Halorhabdus tiamatea: proteogenomics and glycosidase activity measurements identify the first cultivated euryarchaeon from a deep‐sea anoxic brine lake as potential polysaccharide degrader. (27th February 2014) - Werner, Johannes; Ferrer, Manuel; Michel, Gurvan; Mann, Alexander J.; Huang, Sixing; Juarez, Silvia; Ciordia, Sergio; Albar, Juan P.; Alcaide, María; La Cono, Violetta; Yakimov, Michail M.; Antunes, André; et al.
Summary Euryarchaea from the genus Halorhabdus have been found in hypersaline habitats worldwide, yet are represented by only two isolates: Halorhabdus utahensis AX‐2T from the shallow Great Salt Lake of Utah, and Halorhabdus tiamatea SARL4BT from the Shaban deep‐sea hypersaline anoxic lake (DHAL) in the Red Sea. We sequenced the H. tiamatea genome to elucidate its niche adaptations. Among sequenced archaea, H. tiamatea features the highest number of glycoside hydrolases, the majority of which were expressed in proteome experiments. Annotations and glycosidase activity measurements suggested an adaptation towards recalcitrant algal and plant‐derived hemicelluloses. Glycosidase activities were higher at 2% than at 0% or 5% oxygen, supporting a preference for low‐oxygen conditions. Likewise, proteomics indicated quinone‐mediated electron transport at 2% oxygen, but a notable stress response at 5% oxygen. Halorhabdus tiamatea furthermore encodes proteins characteristic for thermophiles and light‐dependent enzymes (e.g. bacteriorhodopsin), suggesting that H. tiamatea evolution was mostly not governed by a cold, dark, anoxic deep‐sea habitat. Using enrichment and metagenomics, we could demonstrate presence of similar glycoside hydrolase‐rich Halorhabdus members in the Mediterranean DHAL Medee, which supports that Halorhabdus species can occupy a distinct niche as polysaccharide degraders in hypersaline environments.